The Roles of Exosomes in Visual and Auditory Systems - Jiang, Pei; Zhang, Shasha; Cheng, Cheng; Gao, Song; Tang, Mingliang; Lu, Ling; Yang, Guang; Chai, Renjie (Frontiers in Bioengineering and Biotechnology, 2020)
Exosomes are nanoscale membrane-enclosed vesicles 30-150nm in diameter that are originated from a number of type cells by the endocytic pathway and consist of proteins, lipids, RNA, and DNA. Although, exosomes were initially considered to be cellular waste, they have gradually been recognized to join in cell-cell communication and cell signal transmission. In addition, exosomal contents can be applied as biomarkers for clinical judgement and exosomes can as potential carriers in a novel drug delivery system. Unfortunately, purification methods of exosomes remain an obstacle. We described some common purification methods and highlight Morpho Menelaus (M. Menelaus) butterfly wings can be developed as efficient methods for exosome isolation. Furthermore, the current research on exosomes mainly focused on their roles in cancer, while related studies on exosomes in the visual and auditory systems are limited. Here we reviewed the biogenesis and contents of exosomes. And more importantly, we summarized the roles of exosomes and provided prospective for exosome research in the visual and auditory systems.